KONSENTRASI SPASIAL DAN SPESIALISASI SEKTOR EKONOMI WILAYAH - Cut Endang Kurniasih; Bunga Chintia Utami; Ufira Isbah; Sri Endang Kornita; Dahlan Tampubolon (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2021)
This study examines the economic structure of Rokan Hilir Regency from 2011 to 2020 using indicators of localization and specialization in 17 sectors. This study utilizes the Gross Regional Domestic Product data published by the Central Bureau of Statistics of Rokan Hilir Regency. Two models are used empirically: (i) localization quotient and (ii) specialization coefficient. The results of the analysis show that the economic sector of Rokan Hilir Regency relies on the mining and quarrying sector, as well as the agriculture, fishery, and forestry sectors, with the remaining fifteen sectors classified as non-basic. Seventeen economic sectors in Rokan Hilir Regency have a coefficient of specialization less than one, indicating that there is no prominent sector with significant development or specialization between 2011 and 2020.